Hubungan Disiplin Kerja Dengan Kinerja Pegawai di Puskesmas Pintukota Kota Bitung - Ofelia Ersegofina Tahulending; Hi Suwandi Luneto; Tezar Nusi (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2025)
Work discipline is a behavior that must be instilled in every individual inside and outside the organization. Employee performance is influenced by several factors, including work discipline. The purpose of this research is to identify the relationship between work discipline and employee performance at Puskesmas Pintukota Kota Bitung.This research uses quantitative research with a cross sectional study design. Data analysis using Chi-Square with a level of significance (a < 0.05). The population in this study were all employees. With a sample size of 42 respondents obtained by total sampling technique.The statistical test obtained a value of <p=0.012 & 0.001 (a<O.002) on the work discipline variable. This means that Ha is accepted or there is a significant relationship between work discipline and employee performance. The conclusion of this research is that there is a relationship between work discipline and employee performance. The results of this research are expected that Puskesmas employees can maintain and improve work discipline so as to get good performance results in achieving each program that is arranged.